The Gambia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in The Gambia during 1990-95. Economic activity slowed down in 1993/94 and contracted by at least 4 percent in real terms in 1994/95. With the drop in re-export trade and the disruption of the tourist season, domestic government revenues declined by more than 4 percent of GDP during 1993/94-1994/95; foreign grants fell by an additional 2 percent of GDP, owing to the suspension of balance-of-payments assistance following the military coup.